Analysis of Relateel Slide Ratio for Gear Drive and Ways of Advancing Wayr load capacity - Yang Jianzhong(31) (Jixie chuandong)
This paper thinks that the amount of related slide ratio has directive effects on the wear quantity of the low velocity gear and selecting different addendum modification coefficients, modules and addendum coefficients can change the amount of related slide ratio by the theoretic analysis of related slide ratio by the theoretic analysis of related slide ratio for gear drive and the calculation of related slide ratio for several tooth shape parameters.It presents ways of advancing gear′s wear load capacity and corective selecting the addendum modification coefficient.